Thermal response of multi-layer UV crosslinked PEGDA hydrogels - Khalili, Mohammad Hakim; Afsar, Ashfaq; Zhang, Rujing; Wilson, Sandra; Dossi, Eleftheria; Goel, Saurav; Impey, Susan A.; Aria, Adrianus Indrat (Elsevier, 2022)
Poly(ethylene glycol) diacrylate (PEGDA) hydrogels are ubiquitously used in a wide variety of applications in tissue engineering. In this study, the thermal response of multi-layered PEGDA hydrogels was investigated under various conditions of the temperature-controlled environments (8, 20, 37, and 45 °C) through gravimetric and volumetric methods. These multi-layered hydrogels were produced using a computer-controlled projection lithography and compared to the monolithic hydrogels fabricated through bulk photo-crosslinking. It was observed that the volume of multi-layered PEGDA hydrogels increased to about 10% at a temperature of 8 °C, while their volume decreased by 8% and 12% when stored at 37 °C and 45 °C, respectively. PEGDA hydrogel also showed an anisotropic characteristic where the axial dimensional change was about 43% higher than the lateral dimension. This finding is critical to inform the design and fabrication of PEGDA hydrogels to compensate for the axial and lateral volume changes during the application at different temperatures.
Keywords: Poly (ethylene glycol) diacrylate; Projection lithography; Thermoresponsive hydrogel; Multi-layered structures